Studi kohort prevalensi obesitas siswa siswi sekolah lanjutan tingkat pertama (SLTP) Kota Yogyakarta - Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: The prevalence of obesity is continuously in-creasing both in developed and developing countries. This increasing prevalence of obesity may be associated with the increasing exposure to obesogenic environment.Objective: To know the trend of obesity prevalence among Rural Junior High School in YogyakartaMethod: This cohort study was conducted in Yogyakarta at 2003 from August to October and at 2005 from June to September.Result: The prevalence of obesity in 2003 showed 7.3% and 10.3% in 2005. Thus, it increased 3% during 2 years. But prevalence of obesity was not increased among 1440 students who followed body mass index percentile based on center for chronic disease (CDC) 2000.Conclusion: During 2 years, the change of obesity status had not significantly shown because obesity occurred in a long period. While the increasing obesity prevalence occurred.